Spatial And Temporal Characterization Of 433mhz Radio Base Wsn In Outdoor Environment (International Journal of Engineering and Computer Science, 2015)
In this paper 433MHz radio (KYL500s) based Wireless Sensor Network (WSN) is used in an experimental testbed to investigate spatial and temporal  variations of the packet error rate which is a wireless link quality metric in order to determine the link quality. The packet error rate measurements were taken at intervals of 10 meters up to a distance of  600meters in 0o, 90o, 180o and 270o  directions and the results obtained show that the packet error rate increases with distance. The experimental WSN was set up for the whole day and the measurement of packet error rate variation with time was taken at fixed wireless sensor distances of 50meters, 100meters, 150meters, 200meters, 250meters,  300meters, 350meters, 400meters,450meters,500meters, 550meters and 600meters  from the sink. The temporal result showed that the link quality is worse at approximately 10.00 and 17.00 hours period.